The Effect of STEAM Learning and Scientific Attitude on Students' Creative Thinking Skills - Halimatus Sakdiah; Fajrul Wahdi Ginting; Nimas Sri Rezeki; Agustina Miranda (LPPM Universitas Malikussaleh, 2022)
Facing the development of 21st -century technology, students must be equipped with skills that help them become superior human resources, one of which is creative thinking skills. Creative thinking skills are the ability to analyze something based on data or information to generate new ideas in understanding something. One way to improve creative thinking skills is to train students to explore scientific attitudes and carry out learning that applies scientific activities such as STEAM learning (science, technology, engineering, art, and mathematics). This study uses a quantitative research method Pre-Experimental Design. The design used is the One Group Pretest-Postest Design. The instruments used were twin observations during STEAM learning to assess creative thinking skills and questionnaires to assess scientific attitudes. The test used is a simple regression test that produces the equation Y=3.51+1.21X. Test the hypothesis using the t-test which concludes that there is a significant influence of scientific attitude on the creative thinking skills of students who apply STEAM learning.